THE REAL STEP IN CONVERGENCE PROJECT: A PARADIGM SHIFT FROM REVENUE RECOGNITION TO REVENUE FROM CONTRACTS WITH CUSTOMERS - DALKILIC, Ali Fatih (International Journal of Contemporary Economics and Administrative Sciences, 2015)
Revenue is a crucial number to users of financial statements in assessing an entity’s financial performance and position. In May 2014, the IASB and FASB published a new joint standard (IFRS 15 vs. ASC 606) on revenue recognition which replaces most of the detailed guidance on revenue recognition that currently exists under US GAAP and IFRS. The new rules will apply to all entities that enter into contracts with customers. Coming up with a joint standard about recognizing revenue is a major achievement for the standard setters, but for corporate world the real work is fast approaching. According to first introduction paragraph of the standard IFRS 15 establishes principles for reporting useful information to users of financial statements about the nature, amount, timing and uncertainty of revenue and cash flows arising from an entity’s contracts with customers. Adoption of the joint standard on revenue recognition will represent a major advancement toward the ultimate goal of creating one set of high quality international accounting standards. The purpose of this study is two-fold: first to highlight the history and background of the new standard; second to make some policy recommendations for companies towards preparation for new standard.